Мифологизм ХХ аср адабиётининг энг характерли ҳодисаси - Жовлиев, Б (SCIENCE and SOCIETY, 2018)
The article analyses the impact of various traditions and styles in the prosaic genre of world literature on the develop- ment of Uzbek national literature (prose). Based on the works of the writer Nazar Eshonkul it proves the absorption of lead- ing mythological approaches, mythopoetic images and interpretations in the world literature of the 20th century into the national literature.
Keywords: traditions; styles; national prose; national memory; national liberation; assimilation; metaphor; mythologi- cal perception; modernism; mythopoetry; mythological space; century of myths